2021
DOI: 10.1177/0486613420982083
|View full text |Cite
|
Sign up to set email alerts
|

The Long Expansion and the Profit Squeeze: Output and Profit Cycles in Brazil (1996–2016)

Abstract: The present paper argues that the recent Brazilian crisis was related to a cyclical profit squeeze that took place between 2009 and 2014, following the long expansion that started in 2003. To do so, the cyclical trajectories of the output and the profit rate in the Brazilian economy for the period between 1996 and 2016 are examined by resorting to the framework established by Weisskopf (1979). The results indicate that profit squeezes are rare in the Brazilian economy, possibly due to the truncated character o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 54 publications
0
18
0
4
Order By: Relevance
“…By 2008, the profit rate started to fall, and the capacity utilization peaked (Marquetti, Hoff, and Miebach 2020). Some studies found a profit squeeze and a falling profit rate that combined with the peak in capacity utilization that left little space for expansionary policies (Marquetti et al 2019; Marquetti, Hoff, and Miebach 2020; Martins and Rugitsky 2021). In Keynesian fashion, the Brazilian government decided to implement countercyclical policies to fight the great recession.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2008, the profit rate started to fall, and the capacity utilization peaked (Marquetti, Hoff, and Miebach 2020). Some studies found a profit squeeze and a falling profit rate that combined with the peak in capacity utilization that left little space for expansionary policies (Marquetti et al 2019; Marquetti, Hoff, and Miebach 2020; Martins and Rugitsky 2021). In Keynesian fashion, the Brazilian government decided to implement countercyclical policies to fight the great recession.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the state-owned banks’ credit supply soared, leading to a substantial rise in the credit-to-GDP ratio. The government also stimulated household borrowing through a “new kind of credit with automatic repayments from the paycheck” (Martins and Rugitsky 2021), an institutional change that impacted credit markets. Thirdly, the government launched a plan to improve the infrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…Já Martins e Rugitsky (2021) sustentam que a crise brasileira dos anos 2010 esteve relacionada com uma compressão cíclica dos lucros -profit squeeze -entre os anos 2009 e 2014, após a longa expansão iniciada em 2003. Considerado "raridade" na periferia do capitalismo, esse fenômeno pode "ajudar a interpretar a profundidade do colapso que se seguiu", com consequências políticas e econômicas profundas (Martins;Rugitsky, 2021, p. 11). No entender dos autores, a compressão dos lucros agravou o conflito distributivo e pressionou para baixo os investimentos, dinâmica contraposta pela reivindicação de políticas de austeridade pelas classes dominantes.…”
unclassified
“…No entender dos autores, a compressão dos lucros agravou o conflito distributivo e pressionou para baixo os investimentos, dinâmica contraposta pela reivindicação de políticas de austeridade pelas classes dominantes. No final de 2014, a pressão surtiu efeito e Dilma mudou a política econômica, com "contração abrupta dos gastos públicos", que resultou em "grande queda da atividade econômica" (Martins;Rugitsky, 2021, p. 18). Em linha com tal interpretação, Serrano e Summa (2018) afirmam que, entre 2004 e 2014, houve acirramento do conflito distributivo pela tendência "de os salários reais crescerem continuamente acima do crescimento da produtividade" (Serrano;Summa, 2018, p. 176).…”
unclassified
“…Nesse sentido, há vários indícios que apontam para o aumento das tensões distributivas durante este ciclo de crescimento, o que permite supor que as contradições econômicas podem ter produzido efeitos sobre a dinâmica da política institucional (Dweck & Teixeira, 2017;Serrano & Summa, 2018;Marquetti, Hoff & Miebach, 2020;Singer, 2020;Martins & Rugitsky, 2021). De fato, na medida em que a crise econômica ficou evidente, em meados dos anos 2010, foi notável o delineamento de uma crise político-institucional.…”
Section: Introductionunclassified